Profil Career Adaptability Mahasiswa Bidikmisi Universitas Negeri Semarang - Sinta Saraswati; Binti Isrofin; Edwindha Prafitra N (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2017)
This study aimed to find out the profile of Bidikmisi students at Semarang State University (UNNES). This was a quantitative study with descriptive survey design. The subject of this study was 462 university students who were taken by simple random sampling technique. The data were collected by using career adaptability scale.The data were analyzed by using descriptive statistics. Based on the result of the analysis, it was found that the average profile of UNNESS Bidikmisi students’ career adaptability was 51% and was categorized as high. The result of this study shows that the attempts in improving students’ career adaptability by the lecturers, parents, and university counselors are needed